103: EARLY OUTCOMES OF ROBOTIC GASTRECTOMY COMPARED WITH OPEN GASTRECTOMY FOR GASTRIC CANCER WITH DESCRIPTION OF THE ROBOTIC TECHNIQUE. (23rd April 2022) - Jung, M K; Biasco, B; Chevallay, M; Wassmer, C H; Toso, C; Mönig, S P
Abstract: Background and aim: Minimally invasive gastrectomy for gastric cancer shows slower adoption in Western countries, probably due to more advanced stages and a more frequently proximal localization, which requires a total gastrectomy. We aimed to assess the perioperative outcomes in early and locoregional advanced gastric cancer. Methods: We retrospectively reviewed a prospectively collected database. A total of 51 patients who underwent oncologic total gastrectomy or subtotal gastrectomy by robotic or open approach of stage pT1-T4a, pN0–3 were identified from June 2016 until June 2020. Nine patients were operated on robotically, and 42 patients by laparotomy. Results: The age of the patients in the robotic group was comparable to that of the open group (64.7 ± 9.2 versus 62.8 ± 12.9, P = 0.685). Endoscopic tumor size was smaller in the robotic group (24.3 ± 10.4 mm versus 43.1 ± 27.0 mm, P = 0.081). Blood loss was significantly smaller with the robotic approach (185 ± 180 mL versus 425 ± 257 mL, P = 0.038). Pathologic tumor stage included stages pT1–pT4b in the open group, while stages pT1–pT3 were operated by robotic approach. Fewer tumors were localized in the upper body in the robotic group (0, 0%) than in the open group (12, 28.6%). The length of the proximal margin was comparable in the two groups (104.29 ± 50.29 versus 86.88 ± 64.66, P = 0.516). The mean number of retrieved lymph nodes was comparable in the robotic group and the open group (42.89 ± 12.119 versus 43.22 ± 20.271, P = 0.963). The mean number of metastatic nodes was significantly lower in the robotic group (0.33 ± 0.707 versus 7.02 ± 14.313, P = 0.171). Diffuse-type cancers were significantly more frequent in the robotic group (3 (33.3%) versus 3 (8.6%), P = 0.040). Significantly fewer high-grade complications (Clavien>3a) appeared in the robotic group (0 (0%) versus 2 (4.8%), P = 0.019). Length of hospital stay was comparable in the two groups. Conclusion: The gold standard of oncologic gastrectomy is still the open approach. The minimally invasive approach must show comparable pathohistological results in regards to lymph node harvest and proximal tumor margins to be accepted in future European guidelines.